2018
DOI: 10.1111/ans.14796
|View full text |Cite
|
Sign up to set email alerts
|

Post‐mortem general surgeon reflection on decision‐making: a mixed‐methods study of mortality audit data

Abstract: This mixed-methods study has identified a minority of surgeons proffer retrospective management changes after their patient has died. Of those who do, decision-making around operative management is the most common area of reflective consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This reflection is done through Google Forms, where they are not only asked to choose the options, but also to fill out an open-ended answer sheet and the categories of learning difficulties they are experiencing. Exploration activities are carried out using PMA (Post Mortem Analysis) analysis (Cattanach et al, 2018; Goh & Loh, 2013; Kristiansen et al, 2012; Myllyaho et al, 2004; Pan et al, 2019) They were asked about why they had difficulty in learning and how committed they were to overcome the difficulty. The results of data analysis were processed and presented in the form of a fishbone model.…”
Section: Methodsmentioning
confidence: 99%
“…This reflection is done through Google Forms, where they are not only asked to choose the options, but also to fill out an open-ended answer sheet and the categories of learning difficulties they are experiencing. Exploration activities are carried out using PMA (Post Mortem Analysis) analysis (Cattanach et al, 2018; Goh & Loh, 2013; Kristiansen et al, 2012; Myllyaho et al, 2004; Pan et al, 2019) They were asked about why they had difficulty in learning and how committed they were to overcome the difficulty. The results of data analysis were processed and presented in the form of a fishbone model.…”
Section: Methodsmentioning
confidence: 99%
“…Surgeons are becoming more receptive to shared decision-making when deciding to operate. 33 In Australia and the USA, an audit and survey of surgeons reported that 26% would change the decision to operate in retrospect after a death, 34 and that more than half of surgeons would not operate in the context of a do-not-resuscitate order. 35 However, barriers to ACP in surgery remain and include limited community awareness, reluctance of healthcare professional involvement, 36 the short-term nature of surgical goals and planning, limited education in ACP and the inherent nature of resuscitation in anaesthesia.…”
Section: Implications For Clinicians and Policy Makersmentioning
confidence: 99%
“…QASM data offer an opportunity to analyse individual surgeons' reflections, to gain a collective understanding of factors that might have led to improved patient outcomes. Cattanach and co‐workers categorized surgeons' reflections on contributors to patient deaths and found that, with the benefit of hindsight, 18 per cent of 2575 surgeons would have managed their patients differently. Operative and clinical management were the most common areas of reflective change.…”
Section: Introductionmentioning
confidence: 99%